239Pu evaluation comparison study. (August 2018) - Alrwashdeh, Mohammad
Highlights: The analysis of 239 Pu was performed using the SAMMY Code for Neutron Transmission, Capture, and Fission cross-sections in the resolved resonance region up to 2.5 keV. Due to the difficulties of processing large covariance matrices, the evaluations were performed in the following distinct uncorrelated energy regions: 0.0–1.0 keV, 1.0 keV–2.0 keV, and 2.0 keV–2.5 keV. Abstract: The analysis of 239 Pu was performed using the SAMMY Code for Neutron Transmission, Capture, and Fission cross-sections in the resolved resonance region up to 2.5 keV. Due to the difficulties of processing large covariance matrices, the evaluations were performed in the following distinct uncorrelated energy regions: 0.0–1.0 keV, 1.0 keV–2.0 keV, and 2.0 keV–2.5 keV. By using version 8.0.0 of the SAMMY code, the treatment of large resonance parameter covariance matrices was improved significantly. The aim of this work is to analyze the experimental data using a self-developed experimental nuclear data fitting code FITWR and analyze it with the SAMMY code, then compare the results with Bayes method. Finally, the output results from these methods is processed by the SAMMY code in order to obtain covariance matrix resonance parameters in the energy range from 0 to 2.5 keV. All the computational experiments done for this paper was carried out at IMAN1 Center – Jordan's National Supercomputing Center (IMAN1).